Pour une esthétique de l'émancipation: construire les lignées d'un art queer - Alfonsi, Isabelle; Fraisse, Geneviève; Abonnenc, Mathieu K. (Mathieu Kleyebe) (B42, 2019)
"Loin de relire l'histoire de l'art en lui appliquant de façon anachronique le terme « queer », utilisé positivement dans les milieux militants depuis la fin des années 1980, Pour une esthétique de l'émancipation cherche à montrer comment l'écriture de l'Histoire de l'art a minoré l'importance des engagements politiques et affectifs des artistes et rendu inopérante la portée sociale de leurs œuvres. En imaginant des amitiés inédites entre des artistes du passé, Isabelle Alfonsi fait émerger une lignée féministe et queer pour l'art contemporain. Des pratiques artistiques du XXe siècle sont ainsi replacées dans le contexte du militantisme de défense des droits des homosexuel•le•s et de la formation d'une critique radicale féministe et anticapitaliste. Claude Cahun et Michel Journiac croisent l'histoire du minimalisme états-unien, vu à travers Lynda Benglis, Lucy Lippard ou Yvonne Rainer. Les guerres de représentation menées pendant la crise du sida sont lues au prisme des oeuvres de Felix Gonzalez-Torres, du concept de désidentification de José E. Muñoz et de l'activisme culturel du groupe Boy/Girl with Arms Akimbo, dans le San Francisco des années 1980."– Résumé de l'éditeur.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; activisme; approches et analyses; artistes queers; arts; cours; discipline; har4600; histoire de l'art; histoire et politique; militance; premier cycle; périodes historiques; queer; thématiques; émancipation

Art & queer culture - Lord, Catherine; Meyer, Richard (Phaidon, 2019)
Spanning 125 years, Art and Queer Culture is the first major historical survey to consider the ways in which the codes and cultures of homosexuality have provided a creative resource for visual artists. Attempts to trouble the conventions of gender and sexuality, to highlight the performative aspects of identity and to oppose the tyranny of the normal are all woven into the historical fabric of homosexuality and its representation. From Oscar Wilde to Ryan Trecartin, from the molly houses of eighteenth-century London to the Harlem drag balls of the 1920s, the flamboyant refusal of social and sexual norms has fuelled the creation of queer art and life throughout the modern period. Although the book proceeds in a chronological fashion, it does not propose a progressive narrative in which homosexuals become increasingly adept at negotiating the circumstances of censorship and overcoming the terms of stigma and invisibility. The dialogue between art and queer culture does not move towards ever more affirmative images of equality and dignity. Rather than countering homophobia with 'positive' images of assimilation, many of the artists and photographers featured in this book draw upon, and even draw out, the deviant force of homosexuality. Art and Queer Culture includes not only pictures made and displayed under the rubric of fine art but also those intended for private, underground or otherwise restricted audiences. Scrapbooks, amateur artworks, cartoons, bar murals, anonymous photographs, activist posters, all appear in its pages, as do paintings, sculptures, art photographs and video installations. Writing queer culture into the history of art means redrawing the boundaries of what counts as art as well as what counts as history. It means searching for cracks in the partition that separates 'high' art from 'low' culture and in the divide between public achievement and private life
Première publication: 2013
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artistes queers; arts; cours; discipline; europe; fem1000; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; thématiques; états-unis

Transidentités: ordre & panique de genre : le réel et ses interprétations - Espineira, Karine; Bertini, Marie-Joseph (L'Harmattan, 2015)
Engagée dans une recherche sur le terrain transidentitaire, la chercheuse s'attache à croiser état des lieux du terrain associatif et militant trans avec l'histoire des définitions de la médecine légale, mettant à jour la politisation des groupes, les apports des nouveaux médias et les effets de la médiatisation sur les personnes transgenres. Cet ouvrage est complémentaire du titre Médiacultures: la transidentité en télévision, édité simultanément.
Section: 263 pages ; 24 cm.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; approches et analyses; cours; discipline; europe; france; histoire et politique; militance; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2014; sociologie; thématiques; transféminisme

Feminism-art-theory: an anthology 1968-2014 - Robinson, Hilary (Wiley Blackwell, 2015)
"Charting over 45 years of feminist debate on the significance of gender in the making and understanding of art, the long-anticipated new edition of Feminism-Art-Theory has been extensively updated and reworked. Completely revised, retaining only one-third of the texts of the earlier edition, with all other material being new inclusionsBrings together 88 revealing texts from North America, Europe and Australasia, juxtaposing writings from artists and activists with those of academicsEmbraces a broad range of threads and perspectives, from diverse national and global approaches, lesbian and queer theory, and postmodernism, to education and aestheticsIncludes many classic texts, but is particularly notable for its inclusion of rare and significant material not reprinted elsewhereProvides a uniquely flexible resource for study and research due to its scale and structure; each of the seven sections focuses on a specific area of debate, with texts arranged chronologically in order to show how issues and arguments developed over time"–Page 4 de la couverture.
Section: xix, 524 pages ; 26 cm
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; art engagé; art féministe; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; lesbianisme; militance; postmodernisme; premier cycle; pédagogie; périodes historiques; queer; thématiques; théorie de l'art

Questionnements sur la compréhension militantEs libertaires Queer et féministes au Québec à l'égard du Nous femmes et la non-mixité - Fortier, Ashley (Faut-il réfuter le Nous femmes pour être féministe au XXIe siècle?, 2009)
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; cours; débat; fem1000; féminisme libertaire; féminisme queer; histoire et politique; interdisciplinarité; militance; pratiques féministes; premier cycle; périodes historiques; queer; québec; ressource en ligne; régions géographiques; thématiques

Gabriel Girard – Interview Elsa Dorlin : Le Queer est un matérialisme - Girard, Gabriel (Syllepse, 2007)
Interview d'Elsa Dorlin pour l'ouvrage "Femmes, genre, féminismes".
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amériques; approches et analyses; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; philosophie; philosophie politique; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; états-unis

La réflexion queer : apports et limites - Lamoureux, Diane (Dialogues sur la troisième vague féministe, 2005)
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; fem1000; histoire et politique; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; québec; régions géographiques; shm4000; systèmes d'oppressions; thématiques

Mariage gai: les coulisses d'une révolution sociale - Larocque, Sylvain (Flammarion, 2005)
Certains l’ont vu comme le plus important débat social de notre époque, c’est en tout cas une question déchirante, sur laquelle ont dû se pencher la plupart des pays occidentaux. Ce livre raconte l’histoire inédite du mariage gai au Canada : la bataille des arguments juridiques et politiques, les stratégies secrètes et surtout les jeux de coulisses qui ont conduit à cette nouvelle avancée des droits de la personne.Pour témoigner des motivations des couples qui ont amorcé le mouvement, puis des juges et des politiciens qui ont pris le relais, Sylvain Larocque s’appuie sur une trentaine d’entrevues exclusives, y compris avec le premier ministre Paul Martin, des ministres, des conseillers politiques et des avocats. On saisit ce qui a convaincu Jean Chrétien et son successeur d’aller de l’avant avec cette véritable « patate chaude » ; on comprend ce qu’ont ressenti les opposants face à cette redéfinition d’une institution millénaire ; on mesure l’ampleur d’une controverse qui en appelait aux convictions intimes de chacun. Suivant Sylvain Larocque Sylvain Larocque est correspondant parlementaire de La Presse Canadienne à Ottawa. Il a suivi de près les tractations juridico-politiques ayant entouré le mariage homosexuel.
Section: 337 pages ; 23 cm
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; histoire et politique; hétérosexisme; identités LGBTQIA2+; mariage; premier cycle; périodes historiques; queer; québec; régions géographiques; shm4000; systèmes d'oppressions; thématiques

Aimez-vous le queer? - Schehr, Lawrence R. (Rodopi, 2005)
Lawrence Schehr's introduction to this collection of essays covers key landmarks in twentieth-century representations of homosexuality in French literature and culture. Beginning with Gide's and Proust's classical and aristocratic representations of homosexuality, subdued within discourses of power and language consonant with the turn of the century, Schehr proceeds to identify the literary and cinematic innovations of Cocteau and Genet as united in their respective revolt against the totalizing structures and discourses of their illustrious predecessors. After discussing the Second World War, the consumerism of the 1960s, and the emerging ‘culture gay’, Schehr fast-forwards to the advent of the paradox of queer theory in the 1990s, highlighting its theoretical (mis)appropriations, from the positive critique of heteronormativity to its insignificance ‘pour le séropositif mourant dans un lit d'hôpital’ (p. 10), acknowledging along the way that queer theory is both ‘made in the USA’ (p. 11) and subject to that continent's imperializing tendencies and ancillary oversights. The editor promises queer readings of French literature and film, but then proffers post-queer readings. Many of the contributions are stimulating and rich in insights. Owen Heathcote's study of the military uniform as both mask and precursor of the collapse of masculinity in novels by Balzac and the cinema of Claire Denis earmarks the uniform as the queerizing stuff of maleness. James Williams's exploration of Jean Cocteau's influence on the cinema of Jean-Luc Godard also unearths a queerization at the heart of Godard's aesthetic creation. In a fascinating contribution, Elizabeth Stephens deconstructs the ‘wall’ of repression and solitude (and its associations with closeted representations of homosexuality) in order to expose the ‘fissures dans les murs genetiens’ (p. 133), demonstrating how Genet subverts categories of heteronormative language in the pursuit of repressed homoerotic desire. Drew Jones conducts a thoroughly lucid exegesis of the distinction between sexual desire (act) and homosexual ‘identity’ in Genet's Querelle de Brest. Countering the Sartrean notion that Genet's treatment of homosexuality (as value in crime and disgust against authority) is not existential (‘homosexuel en soi’ but not ‘pour soi’), Jones argues that Querelle breaks free of essentialist homosexuality by resisting the naming and categorizing hegemony of an Identity as ‘pederast’ that society has conferred on him. It would have been a treat to see how this collection would have evolved had the ‘projet scientifique’ first envisaged been followed through; this ‘projet’ clearly reflected the earlier symmetry of Schehr's tripartite schematization of homosexual cultural production from Proust to queer, but I suspect would have given the collection a different direction. The articles are the collection's real focus, and their value for students and academics with interests in gay and lesbian cultural production in France is unquestionable.
Section: 158 pages ; 24 x 17 cm
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; histoire et politique; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; régions géographiques; shm4000; systèmes d'oppressions; thématiques

Namaji: Two-Spirit Organizing in Montreal, Canada - Meyer-Cook, Fiona; Labelle, Diane (Journal of Gay & Lesbian Social Services, 2004)
This article traces the authors' involvement in Two-Spirit organizing in Montreal since 1995. The term Two-Spirit is often used by lesbian, gay, bisexual and transgendered (LGBT) people of Aboriginal descent in both the U.S. and Canada. The authors explore the multifaceted aspects of organizing within a Two-Spirit community. They begin with an examination of contemporary challenges facing Two- Spirit people within Canadian society and then provide several concrete examples of local organizing, ranging from the creation of an educational video on HIV/AIDS and participation in a collaborative project with a school of social work to national and international alliance-building.
Publisher: Taylor & Francis
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; militance; montréal; personnes bispirituelles; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; travail social; études gaies et lesbiennes

Dictionnaire des cultures gays et lesbiennes - Eribon, Didier; Haboury, Frédéric; Lerch, Arnaud (Larousse, 2003)
Dictionnaire illustré et international consacré aux cultures gays et lesbiennes contemporaines (depuis la fin du XIXe siècle). Plus de 570 articles(2 millions de signes en tout), dont 50 dossiers thématiques, qui couvrent tous les aspects du sujet : - références culturelles et artistiques communes (d'Absolutely Fabulous à Virginia Woolf, de Pedro Almodóvar à Andy Warhol.), - associations (Act Up.), - théoriciens (Michel Foucault.), - événements (Lesbian and Gay Pride.), - mours et modes de vie (sida, sexualités.), - aspects légaux (couple, adoption.), - gay and lesbian studies (histoire, sociologie, queer theory.), etc.
Section: 548 pages : illustrations (certaines en couleur), photogr. (certaines en couleur) ; 27 cm
Keywords: 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; histoire et politique; militance; outils; ouvrages de références; premier cycle; périodes historiques; queer; sexualité; soc2014; thématiques; études gaies et lesbiennes

L'union civile: nouveaux modèles de conjugalité et de parentalité au 21e siècle : actes du colloque du Groupe de réflexion en droit privé - Lafond, Pierre-Claude; Lefebvre, Brigitte; Université du Québec à Montréal Groupe de réflexion en droit privé. (Éditions Y. Blais, 2003)
Textes présentés lors d'un colloque organisé par le Groupe de réflexion en droit privé et tenu à la Faculté de science politique et de droit de l'Université du Québec à Montréal, le 10 octobre 2002.
Section: xiv, 399 pages : illustrations ; 23 cm
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits; histoire et politique; identités LGBTQIA2+; militance; premier cycle; périodes historiques; queer; québec; régions géographiques; shm4000; systèmes d'oppressions; thématiques